Burden of early hospitalization after simultaneous liver–kidney transplantation: Results from the US Multicenter SLKT Consortium. Issue 11 (4th July 2022) - Sharma, Pratima; Xie, Jiaheng; Wang, Leyi; Zhang, Min; Magee, John; Answine, Adeline; Barman, Pranab; Jo, Jennifer; Sinha, Jasmine; Schluger, Aaron; Perreault, Gabriel J.; Walters, Kara E.; et al.
Abstract: The burden of early hospitalization (within 6 months) following simultaneous liver–kidney transplant (SLKT) is not known. We examined risk factors associated with early hospitalization after SLKT and their impact on patient mortality conditional on 6‐month survival. We used data from the US Multicenter SLKT Consortium cohort study of all adult SLKT recipients between 2002 and 2017 who were discharged alive following SLKT. We used Poisson regression to model rates of early hospitalizations after SLKT. Cox regression was used to identify risk factors associated with mortality conditional on survival at 6 months after SLKT. Median age ( N  = 549) was 57.7 years (interquartile range [IQR], 50.6–63.9) with 63% males and 76% Whites; 33% had hepatitis C virus, 20% had non–alcohol‐associated fatty liver disease, 23% alcohol‐associated liver disease, and 24% other etiologies. Median body mass index (BMI) and Model for End‐Stage Liver Disease–sodium scores were 27.2 kg/m 2 (IQR, 23.6–32.2 kg/m 2 ) and 28 (IQR, 23–34), respectively. Two‐thirds of the cohort had at least one hospitalization within the first 6 months of SLKT. Age, race, hospitalization at SLKT, diabetes mellitus, BMI, and discharge to subacute rehabilitation (SAR) facility after SLKT were independently associated with a high incidence rate ratio of early hospitalization. Number of hospitalizations within the first 6 months did not affect conditional survival. Early hospitalizations after SLKT were very common but did not affect conditional survival. Although most of the risk factors for early hospitalization were nonmodifiable, discharge to SAR after initial SLKT was associated with a significantly higher incidence rate of early hospitalization. Efforts and resources should be focused on identifying SLKT recipients at high risk for early hospitalization to optimize their predischarge care, discharge planning, and long‐term follow‐up.